The Implementation Of Critical Thinking In 21ST Century Learning For Islamic Education - Zulvia Trinova; Dinasril Amir; Pitri Andayani (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
The purpose of this study is to find out how to apply critical thinking in 21st century learning in Islamic Education at SMPN 5 Gunung Talang, Solok. This research is a field research with qualitative descriptive methods. Based on research on the application of critical thinking in 21st Century learning in Islamic Education. The application of critical thinking is seen from the ability of students when thinking critically, students are more active and eager to ask questions, discuss in solving a problem or finding solutions to those problems